2010
DOI: 10.1262/jrd.09-150k
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Changes in the Corpus Luteum During Early Pregnancy in the Cow

Abstract: Abstract. The present study determined vascular changes in the bovine corpus luteum (CL) at Day 16 (early maternal recognition period) and Day 40 in early pregnancy and compared them to the CL from Day 12 and Day 16 of the estrous cycle. The CLs were analyzed in the central and peripheral regions, where site-depending features of vessels and angiogenic factors are evident. The same protein level of the endothelial cell marker von Willebrand factor was retained in the CL from Day 16 of the estrous cycle to Day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
3
16
0
1
Order By: Relevance
“…To collect the CL samples, 11 normal cyclic non-lactating German Holstein cows were used, in a similar way to our previous in vivo study in Germany (Beindorff et al 2010).…”
Section: Collection Of the Bovine CL And Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…To collect the CL samples, 11 normal cyclic non-lactating German Holstein cows were used, in a similar way to our previous in vivo study in Germany (Beindorff et al 2010).…”
Section: Collection Of the Bovine CL And Plasmamentioning
confidence: 99%
“…Ovariectomy was performed on day 16 (nZ4) of the oestrous cycle (not inseminated) as well as on day 16 (nZ7) of pregnancy. Collection of the ovaries was conducted by laparotomy (Beindorff et al 2010). After administration of epidural anaesthesia (2% procaine hydrochloride, Procasel, Selectavet, Weyarn-Holzolling, Germany), the long incision line was infiltrated subcutaneously and intramuscularly with 2% procaine hydrochloride with epinephrine (Isocain, Selectavet).…”
Section: Collection Of the Bovine CL And Plasmamentioning
confidence: 99%
“…The data indicate that CL function is able to persist for a significant amount of time with the interference of PGF 2α . We have previously shown that luteal mRNA expressions of angiogenic factors such as VEGF 120 and VEGF 164 , fragments of VEGF-A, do not differ between the late luteal phase and early pregnancy, while histological examination showed that angiogenesis does not occur in the CL during early pregnancy [42]. This finding is in agreement with the present study, where VEGF-A did not differ among the persistent CL, cyclic CL and CL of pregnancy, indicating that angiogenesis does not occur in the persistent CL or CL of pregnancy.…”
Section: Discussionmentioning
confidence: 96%
“…Seven normal cyclic German Holstein cows were used as in previous in vivo study in Germany (Beindorff et al 2010). Briefly, the animals were divided into four groups: ovariectomy was performed on days 12 and 16 (C12 and C16, nZ5) of the estrous cycle (not inseminated) as well as on days 16 and 40 (P16 and P40, nZ5-7) of pregnancy.…”
Section: Cls During Early Pregnancymentioning
confidence: 99%
“…The development of the bovine CL is accompanied by active angiogenesis, and the structure of blood vessels is retained during pregnancy (O'Shea et al 1989, Lei et al 1991, Beindorff et al 2010. Leukocytes, including monocytes/macrophages, granulocytes, and T lymphocytes, are localized to the CL in several species (Standaert et al 1991, Brannstrom et al 1994, Reibiger & Spanel-Borowski 2000.…”
Section: Introductionmentioning
confidence: 99%